(untitled) (Research, Society and Development, 2024)
The inappropriate use of medicines can be dangerous, causing adverse events and increasing the risks of medical interventions, resulting in iatrogenesis. This problem is evidenced by an alarming 54,769 deaths due to adverse events, of which 36,174 could have been avoided. Drug Information Centers (DIC) have stood out as effective solutions for disseminating technical and scientific information to promote the wise use of medicines. They are linked to the triad of teaching, research and extension, complementing the academic training of pharmacy students, as suggested by the national curriculum guidelines. This study aimed to establish a DIC in an academic environment, the University Pharmacy of the Faculty of Pharmacy (FU-UFJF) in Juiz de Fora, MG, as an educational pharmaceutical service. The first stage of this process involved gathering information from primary and secondary sources to meet the needs of the community, particularly related to treating COVID-19 and tackling fake news. DIC collaborated with various professionals, including teachers, students, pharmacists, nutritionists and extension fellows, as well as external partners such as the scientific journal JAPHAC, the Faculty of Nutrition and Radio FACOM-UFJF. Radio programs and social media posts were created to share information about COVID-19, resulting in a gradual increase in the dissemination of this information and positive public understanding. This work highlights the importance of cooperation between society, the scientific community and health professionals in promoting health education and improving its indicators.